Using Brainpower in the Classroom - Garnett, Steve (Taylor & Francis, 2005)
This book offers a realistic, practical and accessible model to allow teachers to incorporate the best of recent brain-based research into their teaching. The five steps involve: making learning multi-sensory ensuring activities match the dominant intelligence of the learner matching types of learning to the gender of pupils using the lesson structure to fit the natural attention span of the brain managing the classroom environment to make it brain-friendly and active in supporting learning. Illustrated throughout with classroom examples from a wide range of subject areas, the book is highly practical in its focus and the ideas it contains can easily be adapted to work with all age ranges and types of school.